Decentralized Integral Nested Sliding Mode Control for Time Varying Constrained Modular and Reconfigurable Robot - Bo Dong; Yuanchun Li (Advances in Mechanical Engineering, 2015)
This paper presents a novel decentralized integral nested sliding mode control approach for a time varying constrained modular and reconfigurable robot (MRR) and addresses the problem of joint trajectory tracking control of the MRR with strongly coupled model uncertainty. First, the dynamic model of the time varying constrained MRR is described as a synthesis of interconnected subsystems. Second, a decentralized control scheme is proposed based on only local dynamic information of each module. An integral nested sliding surface is implemented to reduce the chattering effect of the controller. Model uncertainties, including the unmodeled subsystem dynamics, the friction modeling error, and the interconnected dynamic coupling, are compensated by a variable gain supertwisting algorithm (VGSTA) based controller. The stability of the close-loop system is proved using the Lyapunov theory. Finally, simulations are performed for a time varying constrained 2-DOF MRR to study the effectiveness of the proposed method.